SUPERVISION FOR PEDAGOGUES – CAREER COUNSELLORS - Burceva, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Pedagogues-career counsellors perform diverse tasks at schools, and supervision is a new tool for educating and supporting these specialists. The purpose of the article is to carry out a quantitative study on the use of supervision in the professional development of pedagogues-career counsellors and to analyse the results. Study method — structured written questionnaire. The study's results show that pedagogues-career counsellors are satisfied with supervision. They think it is an appropriate form of professional development. Respondents are positive about the methods used in supervision. The main benefits of supervisions (in  pedagogues – career counsellors opinion) are following: supervisions helps to become aware of strengths and weaknesses, promotes motivation at work, educates on various aspects of professional activity, promotes professional development, helps to more clearly define goals, helps to achieve the goals set, helps to prioritize, increases self-confidence, affects behavior, changes attitude, helps to understand the causal relationships, helps to become aware of personal resources, develops thinking etc.